Impoliteness and Gender: An Analysis Of Animation Series Family Guy Season 20th - Fiona Puspitasari Mulyadi; Ratini Setyowati; Rahmaditya Khadifa Abdul Rozzaqwijaya (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study examines the use of impoliteness strategies and their relationship with gender in the animated series "Family Guy," with a specific focus on the 20th season. The objective is to determine whether the creators differentiate the use of impolite language between male and female characters and which gender employs these strategies more frequently. Using Jonathan Culpeper's 1996 frameworks, impoliteness strategies were categorized into five types: bald on record, positive impoliteness, negative impoliteness, sarcasm, and withhold politeness. A qualitative descriptive method was employed to analyse dialogues transcribed from the animations. The findings reveal six instances of impoliteness from Lois Griffin, including three bald on record utterances, two positive incivility utterances, and one withhold politeness utterance. In contrast, Peter Griffin exhibited 11 instances of impoliteness, consisting of one bald on record utterance, six positive impoliteness utterances, one negative impoliteness utterance, and three sarcastic utterances, with no examples of withhold politeness. The analysis indicates that female characters' impoliteness utterances are fewer than male characters, potentially due to limited screen time. However, the nature of Lois Griffin's impoliteness was similar to Peter's, suggesting that the creators did not design female characters to be more polite. This challenges traditional gender stereotypes regarding language use.